A Critical Review on Manjisthadi Taila Varti. - Saini, Rahul; Gupta, Rajesh (International Research Journal of Ayurveda & Yoga, 2023)
Manjishthadi Taila Varti is an Ayurvedic drug mentioned in Bhesajayaratnavali. The main Content Manjishthadi Taila Varti of is the Manjista along with murva and chandana and tila taila indicated in Varna shodhana. The main contents of Manjishthadi Taila Varti is purified Manjista having as varnya (beneficial for complexion), swarya (improves voice), jvarahara (reduces fever), vishaghna (detoxifies), kushthaghna (useful in skin disorders), raktavikarhar (beneficial in blood disorders), vranahar (wound healing), pramehaghna (useful in diabetes), shothahar (anti-inflammatory), yoni-netra and karnavikarhar (useful in uterine -eye and ear disorders), Arshoghna (cures piles) etc. are well described. Therefore from above descriptions it is clear that it possesses Tikta rasa and is used in pittaja Roga. Descriptions in classics explain about rasa and treatment modalities. It is said that Valkasutra (fibre from bark) of Murva is strong and it is used in Vranaseevana. Descriptions in classics explain about rasa and treatment modalities. It is said that Valkasutra (fibre from bark) of Murva is strong and it is used in Vranaseevana. It possesses Tikta Ras, used in Pittaja Roga. Based on descriptions of Nighantu it is a Latha Roopa Vanaspathi (climber) which possess Tikta rasa based on synonym like Tiktavalli. Also other synonyms like Triparni, Peeluparni mentioned led to controversy. Few Nighantu gave synonym like Madhurarasa which gives a hint of Madhura Rasa. Therefore from descriptions it can be concluded the drug possess Tikta, Madhura Rasa and Madhura Vipaka.